RETRACTED: Risk management and the formation of stress tolerance in the organization of entrepreneurial activity - Mushketova Natalia; Shokhnekh Anna; Zakharchenko Flor; Marusinina Elena (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001